Surface Structures, Particles, and Fibers of Shape-Memory Polymers at Micro-/Nanoscale - Liangliang Cao; Liwei Wang; Cihui Zhou; Xin Hu; Liang Fang; Yaru Ni; Chunhua Lu; Zhongzi Xu (Advances in Polymer Technology)
Shape-memory polymers (SMPs) are one kind of smart polymers and can change their shapes in a predefined manner under stimuli. Shape-memory effect (SME) is not a unique ability for specific polymeric materials but results from the combination of a tailored shape-memory creation procedure (SMCP) and suitable molecular architecture that consists of netpoints and switching domains. In the last decade, the trend toward the exploration of SMPs to recover structures at micro-/nanoscale occurs with the development of SMPs. Here, the progress of the exploration in micro-/nanoscale structures, particles, and fibers of SMPs is reviewed. The preparation method, SMCP, characterization of SME, and applications of surface structures, free-standing particles, and fibers of SMPs at micro-/nanoscale are summarized.